Selective inhibition of extra-synaptic α5-GABAA receptors by S44819, a new therapeutic agent. (October 2017) - Etherington, Lori-An; Mihalik, Balázs; Pálvölgyi, Adrienn; Ling, István; Pallagi, Katalin; Kertész, Szabolcs; Varga, Péter; Gunn, Ben G.; Brown, Adam R.; Livesey, Matthew R.; Monteiro, Olivia; Belelli, Delia; et al.
Abstract: In the mammalian central nervous system (CNS) GABAA receptors (GABAA Rs) mediate neuronal inhibition and are important therapeutic targets. GABAA Rs are composed of 5 subunits, drawn from 19 proteins, underpinning expression of 20–30 GABAA R subtypes. In the CNS these isoforms are heterogeneously expressed and exhibit distinct physiological and pharmacological properties. We report the discovery of S44819, a novel tricyclic oxazolo-2, 3-benzodiazepine-derivative, that selectively inhibits α5-subunit-containing GABAA Rs (α5-GABAA Rs). Current α5-GABAA R inhibitors bind to the "benzodiazepine site". However, in HEK293 cells expressing recombinant α5-GABAA Rs, S44819 had no effect on 3 H-flumazenil binding, but displaced the GABAA R agonist 3 H-muscimol and competitively inhibited the GABA-induced responses. Importantly, we reveal that the α5-subunit selectivity is uniquely governed by amino acid residues within the α-subunit F-loop, a region associated with GABA binding. In mouse hippocampal CA1 neurons, S44819 enhanced long-term potentiation (LTP), blocked a tonic current mediated by extrasynaptic α5-GABAA Rs, but had no effect on synaptic GABAA Rs. In mouse thalamic neurons, S44819 had no effect on the tonic current mediated by δ-GABAA Rs, or on synaptic (α1β2γ2) GABAA Rs. In rats, S44819 enhanced object recognition memory and reversed scopolamine-induced impairment of working memory in the eight-arm radial maze. In conclusion, S44819 is a first in class compound that uniquely acts as a potent, competitive, selective antagonist of recombinant and native α5-GABAA Rs. Consequently, S44819 enhances hippocampal synaptic plasticity and exhibits pro-cognitive efficacy. Given this profile, S44819 may improve cognitive function in neurodegenerative disorders and facilitate post-stroke recovery. Highlights: S44819 acts via a unique site on the α5-GABAA R to competitively inhibit GABA binding. S44819 inhibits mouse hippocampal tonic, but not phasic inhibition & facilitates LTP. In rats S44819 enhanced novel object recognition & spatial working memory. This novel α5-GABAA R site offers a new target to treat cognitive disorders & stroke. S44819 has successfully completed a phase1 clinical trial.